The ZEW combined microsimulation-CGE model: innovative tool for applied policy analysis - Markus Clauss; Stefanie Schubert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This contribution describes the linkage of microsimulation models and computable general equilibrium (CGE) models using two already established models called "STSM" and "PACE-L" used by the Centre for European Economic Research. This state of the art research method for applied policy analysis combines the advantages of both model types: On the one hand, microsimulation models allow for detailed labor supply and distributional effects due to policy measures, as individual household data is used. On the other hand, by using a general equilibrium framework, labour market responses, such as wage and labour demand reactions are taken into account.
Keywords: C68; C81; D58; J22; J23; 330; microsimulation; applied CGE analysis; linked micro-macro models; Mikrosimulation; CGE-Modelling; Wirtschaftspolitische Wirkungsanalyse; Theorie